The daily child care from the perspective of Winnicott - Mello, Débora Falleiros de; Antonietto, Ana Carolina Gomes; Furtado, Maria Cândida de Carvalho; Wernet, Monika; Alves, Juliana de Jesus (Rev Rene, 2012)
The purpose of the present study is to describe the way children under 2 years of age are daily taken care of as seen by their mothers in order to provide support to practices and knowledge in child health in the context of primary health care. A descriptive exploratory study was carried out with qualitative data analysis from the perspective of Winnicott‟s approach based on taped interviews with 17 mothers. The results are organized into the following different categories: maternal responsibility and child care; child care and its environment; comfort and interaction in the family. It was possible to grasp the meanings of everyday experiences as discussed in the light of Winnicott‟s approach of the “good-enough mother”, holding, enabling environment and transitional space. It is important for health professionals who are supporting mothers and families to know aspects related to the routine of maternal care, thus providing skilled and humanitarian assistance.